THE IMPACT OF PVA CONCENTRATION ON THE PHYSICAL QUALITY OF THE Eleutherine palmifolia (L.) Merr LEAVES PEEL-OFF GEL MASK - Kumalasari, Eka; Prihandiwati, Erna; Ma'ruf, Muhammad; Ariani, Novia; Amelia, Senya Puteri; Fawwazi, Muhammad Hafizh Abiyyu Fathin (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
The natives of Central Kalimantan utilize Eleutherine palmifolia (l.) Merr as a traditional medicine to treat various diseases. Eleutherine palmifolia  leaves are rich in flavonoid substances. Eleutherine palmifolia  leaves extract has an IC50 value of 45.33 ppm, indicating significant antioxidant activity. Antioxidants are helpful in reducing the risk of UV radiation-induced skin damage. Eleutherine palmifolia leaves have antioxidant properties that can be used as a peel-off gel mask. Polyvinyl alcohol (PVA) bases come in various formulations for peel-off gel mask that F1 10%, F2 12%, and F3 14%. The concentration of PVA is the most significant element affecting how well peel-off gel masks create films. This study aims to determine the impact of PVA concentration on the physical of the Eleutherine palmifolia  leaves Peel-off gel mask. All formulas are tested for organoleptics, homogeneity, spreadability, pH value, and drying speed. The results showed that all peel-off gel mask compositions pass the physical properties test. A one-way ANOVA statistical analysis reveals a significant variation in the preparations drying speeds (p<0,05).